2016
DOI: 10.1136/bcr-2016-216774
|View full text |Cite
|
Sign up to set email alerts
|

Activation ofCytomegaloviruscorneal endotheliitis following laser in situ keratomileusis

Abstract: A case of Cytomegalovirus (CMV) corneal endotheliitis following laser in-situ keratomileusis (LASIK) is presented. A 32-year-old man presented 3 weeks after uncomplicated myopic LASIK with unilateral LASIK flap oedema, interface fluid accumulation, keratic precipitates, anterior uveitis and raised intraocular pressure. Despite treatment with topical corticosteroids, he had 3 further recurrent episodes. Specular microscopy showed decreased endothelial cell density and aqueous humour. Polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…53 The patient had no known history of CMV and activation was believed to be due to local immunosuppression secondary to the steroids received, similar to cases seen after cataract surgery and corneal transplantation. 53,62,63 A similar case reported by Bacsal et al discussed a patient with anterior uveitis and increased IOP two months after LASIK. The patient was eventually diagnosed with CMV uveitis and treated with oral valganciclovir and topical rimexolone for 10 weeks.…”
Section: Post Refractive Surgery Reactivation Of Other Human Herpes Vmentioning
confidence: 58%
See 1 more Smart Citation
“…53 The patient had no known history of CMV and activation was believed to be due to local immunosuppression secondary to the steroids received, similar to cases seen after cataract surgery and corneal transplantation. 53,62,63 A similar case reported by Bacsal et al discussed a patient with anterior uveitis and increased IOP two months after LASIK. The patient was eventually diagnosed with CMV uveitis and treated with oral valganciclovir and topical rimexolone for 10 weeks.…”
Section: Post Refractive Surgery Reactivation Of Other Human Herpes Vmentioning
confidence: 58%
“…52 However, only three case studies were found in the literature demonstrating reactivation of CMV and VZV after corneal refractive surgery. [53][54][55] The reactivation of VZV occurred two months after LASIK, with the patient making a full recovery after treatment with valacyclovir 500 mg twice daily and topical acyclovir twice daily. 54 In a separate case report, Kaufman et al reported a patient with a previous corneal scar due to herpes zoster ophthalmicus (HZO) who underwent PTK, PRK, and LASIK without reactivation.…”
Section: Post Refractive Surgery Reactivation Of Other Human Herpes Vmentioning
confidence: 99%
“…16 Previous reports observed that surgical trauma can cause infection in a case with no previous history of viral eye disease. 17,18 Tan et al 7 reported the occurrence of corneal endotheliitis 3 weeks following laser in situ keratomileusis. Viral endotheliitis or keratitis after cataract surgery has previously been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical trauma can lead to infection in cases with no previous history of viral eye disease. [7][8][9][10][11][12] Endotheliitis following cataract surgery is a rare condition. 13 Herein, we examined a large cohort of patients who underwent cataract surgery and subsequently developed postoperative endotheliitis, providing insights into the incidence and potential risks factors of this disease.…”
mentioning
confidence: 99%